2022
DOI: 10.33369/jeet.6.2.207-221
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Local Culture in English Language Teaching for Papuan Junior High School Students

Abstract: Local culture is a crucial aspect in human life. Local culture relates to the way of human life such as thinking, feeling, and acting. It is undeniable that local culture could be used in the academic context as the medium in learning English. By using local culture, students will be able to empower their ability in thinking, speaking, and writing. Therefore, the teachers are required to design the learning process by providing local culture contents or materials that the students are familiar with. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…A study by Romrome & Ena (2022), in Indonesia found students' motivation and vocabulary levels increased with the incorporation of local cultural topics in the EFL class, as well as critical thinking skills. It was also found that the development of students' English skills including speaking, reading, and writing improved by using local culture content in learning English.…”
Section: Sla Theory By Stephenmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Romrome & Ena (2022), in Indonesia found students' motivation and vocabulary levels increased with the incorporation of local cultural topics in the EFL class, as well as critical thinking skills. It was also found that the development of students' English skills including speaking, reading, and writing improved by using local culture content in learning English.…”
Section: Sla Theory By Stephenmentioning
confidence: 99%
“…Every individual in the world has been raised in a certain culture which has taken individual and collective dimensions (Romrome & Ena, 2022). There is an undeniable link that connects language with culture, as acquiring any language is better accomplished in its cultural sense Alakrash et al, (2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Romrome & Ena (2022), in Indonesia found students' motivation and vocabulary levels increased with the incorporation of local cultural topics in the EFL class, as well as critical thinking skills. It was also found that the development of students' English skills including speaking, reading, and writing improved by using local culture content in learning English.…”
Section: Introductionmentioning
confidence: 99%
“…Every individual in the world has been raised in a certain culture which has taken individual and collective dimensions (Romrome & Ena, 2022). There is an undeniable link that connects language with culture, as acquiring any language is better accomplished in its cultural sense Alakrash et al, (2021).…”
Section: Introductionmentioning
confidence: 99%